Identification of first and second order systems by reset control - S. Zaragoza; J. Sanchez; A. Baños (Revista Iberoamericana de Automática e Informática Industrial RIAI)
The article presents a method for the identification of first and second order processes with time delay using reset controllers in the absence of disturbances. The method is based on compliance with the method of harmonic balance, which implies the use of an approximation of the control reset by its describing function. The FORE controller (First Order Reset Element) with fixed bandwidth has been chosen because it is the easiest reset driver that possesses all the inherent characteristics in this type of drivers and its descriptive function depends on the amplitude and frequency of its sinusoidal signal input. On the other hand, the fact that the behavior of this reset driver depends on of its reset band allows studying the impact of this parameter in the identification process and in its accuracy.